Early Paleozoic ridge subduction in the Chinese Altai: Insight from the abrupt change in zircon Hf isotopic compositions - Sun, Min; Long, XiaoPing; Cai, KeDa; Jiang, YingDe; Wang, BuYun; Yuan, Chao; Zhao, GuoChun; Xiao, WenJiao; Wu, FuYuan (Science China. Earth sciences, 2009)
Zircons were separated from granitoids, gneisses, and sedimentary rocks of the Chinese Altai. Those with igneous characteristics yielded U-Pb ages of 280-2800 Ma, recording a long history of magmatic activity in the region. Zircon Hf isotopic compositions show an abrupt change at ~420 Ma, indicating that prior to that time the magmas came from both ancient and juvenile sources, whereas younger magmas were derived mainly from juvenile material. This may imply that the lithosphere was signifi- cantly modified in composition by a rapid addition of melt from the mantle. We suggest that this dramatic change was due to the onset of ridge subduction, which can account not only for the formation of voluminous granitoids, mafic rocks with complex compositions, and the association of adakite + high-Mg andesite + boninite + Nb-enriched basalt, but also for the coeval high-T, low-P metamorphism.